Sexually Dimorphic Effect of Environmental Enrichment and Weaning on Stress in Piglets - Guadalupe Espejo-Beristain; Pedro Paredes-Ramos; Concepción Ahuja-Aguirre; Apolo Carrasco-García (Animals)
Most intensive swine production systems use invasive practices that increase stress and compromise animal welfare. Apparently, the way in which animals respond to stress is sexually dimorphic. To cope with stress and improve the life of animals, environmental enrichment (EE) is used. The objective of the study was to evaluate how EE and weaning affect the behavior and cortisol levels of barrows and female piglets. Forty piglets were divided into two groups: (1) WEE: piglets that received EE from birth until 21 days of age and whose mothers received EE from week six of gestation until farrowing; (2) NEE: piglets for whom neither them nor their mothers received EE. Cortisol fecal metabolites and frequency, latency and duration of behaviors associated with stress were evaluated and compared before and after weaning. Before weaning, WEE barrows showed less inactive and ingestion behaviors and shorter duration of aggression (p < 0.05), while WEE females showed longer duration of aggression and higher frequency of ingestion behavior (p < 0.05). After weaning, WEE barrows and NEE females had higher cortisol levels, and NEE females showed longer duration of aggression (p < 0.05). In conclusion, piglets’ response to EE and the way they learnt to cope with stress were sexually dimorphic.